Conditions of equilibrium for European option - Kotsiuba, I.B.; Mazur, S.M. (Математичне та комп'ютерне моделювання. Серія: Фізико-математичні науки, 2014)
The article deals with the Black-Scholes model where parameters depend on the time and the environmental state, conditions under which the fair price of an option before and after averaging coincide are considered. Furthermore, the main mathematical characteristics for the fair price of the European call option under the finite discrete-time homogenous Markov chain process are given.